Teaching health promotion: experiences from the University of the Western Cape - P. Struters; M. Phil (AOSIS, 2006)
This article describes and assesses the University of the Western Cape's (UWC) second year Community and Health Science students'experience in their interdisciplinary, community based health promotion module. Health promotion is a rapidly growing discipline for health professionals internationally. The World Health Organisation (WHO) has described health promoting schools as effective settings for the promotion of the health of learners, teachers, parents and the broader community. The health promotion module at UWC introduces the university students to the practical development of health promoting schools. The aim of this study was to assess undergraduate students' attitudes to and impressions of their learning experience during the health promotion module. These interventions included addressing teenage pregnancy; addressing drug abuse including smoking; addressing poor personal hygiene; and addressing the poor classroom environment. Small interdisciplinary teams of students worked with school  learners at a high school in a poorly resourced area in Cape Town, where they planned, implemented and evaluated small scale interventions. Students indicated they had learnt far more from the interdisciplinary, experiential learning than from classroom based learning or textbooks located within their own discipline. The results suggest that health promotion is an ideal subject for physiotherapy students to study collaboratively with the other health disciplines. One group of students wrote: "We have learnt much more than any textbook or lecturer could ever teach us."